Clinical diagnosis of Graves' or non-Graves' hyperthyroidism compared to TSH receptor antibody test. Issue 4 (April 2018) - Bell, Lauren; Hunter, Ann Louise; Kyriacou, Angelos; Mukherjee, Annice; Syed, Akheel A
Abstract : Background: TSH receptor antibody (TRAb) is considered the gold standard diagnostic test for the autoimmunity of Graves' disease (GD), which is commonly diagnosed clinically. Aim: To evaluate the true positive (sensitivity) and true negative (specificity) rates of clinical diagnosis of GD or non-GD hyperthyroidism compared to the TRAb test. Setting: University teaching hospital in North West England. Participants: Patients in the Endocrinology service who had a TRAb measurement between December 2009 and October 2015. Methods: Electronic patient records were studied retrospectively for a pre-TRAb clinical diagnosis of GD or non-GD hyperthyroidism. We examined descriptive statistics and binary classification tests; Fisher exact test was used to analyse contingency tables. Results: We identified 316 patients with a mean age of 45 (range, 17–89) years; 247 (78%) were women. Compared to the TRAb result, clinical diagnosis had a sensitivity of 88%, specificity 66%, positive predictive value 72%, negative predictive value 84%, false negative rate 12%, false positive rate 34%, positive likelihood ratio 2.6 and negative likelihood ratio 0.2 ( P  < 0.0001). Conclusions: Clinicians were liable to both over- and under-diagnose GD. The TRAb test can help reduce the number of incorrect or unknown diagnoses in the initial clinical assessment of patients presenting with hyperthyroidism.